Theorizing financial extraction: The curious case of telephone profits in the Los Angeles county jails - Lara-Millan, Armando (Punishment & society, 2021)
Existing models of financial extraction in the criminal justice system are applied to the case of profitable telephone contracts in the Los Angeles County jails during the mid-1990s. The case exemplifies instances of a “punishment” model of monetary sanctions, in which profits are derived for crime control purposes, and a “predation” model, in which inmates are seen as potential resources to absolve fiscal crisis and create market opportunities. However, the case contains an additional element: legal demand concerning inmates’ mental health care treatment. It is shown that telephone profits in jails could not have been used for predation or punishment purposes without the exploitation of legal ambiguity around inmate’s healthcare. Broader implications for the study of financial extraction as a constitutive theory – one that is both historical causal explanation and generalizable description – are drawn.